Gender beliefs and legitimization of dating violence in adolescents - Ferreira Sónia Brás; Ferreira Mayana Bonfim; Gomes Nadirlene Pereira; Carvalho Amâncio António de Sousa (Open Medicine)
Knowing the gender beliefs (GB) that legitimize dating violence (DV) it is important for the prevention of this phenomenon. The aim is to evaluate the impact of GB interventions that legitimize DV.